2017
DOI: 10.1002/jctb.5484
|View full text |Cite
|
Sign up to set email alerts
|

Mixing characteristics, cell trajectories, pressure loss and shear stress of tubular photobioreactor with inserted self‐rotating helical rotors

Abstract: BACKGROUND Tubular photobioreactors (TPBRs) have great potential in culturing microalgae, but their poor mixing properties make it difficult to increase the surface productivity. In this work, a TPBR with inserted self‐rotating helical rotors, which have been under study for a decade, was designed. RESULTS This paper aimed to show hydrodynamic behaviors of gas–liquid in a TPBR with inserted self‐rotating helical rotors by computational fluid dynamics (CFD) and visualization experiments. It can be concluded tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As shown in Figure , remarkable turbulent flow mixing was found on the bottom culture surface where the spray culture spattered, and the area of turbulent flow was estimated to be approximately one-fifth of the total cultivation area. This result indicated that the proposed mixing mode could significantly increase the light-dark cycling frequency and mixing performance in a certain mixing time and k L a (O 2 ) (Figure ); light-dark cycling is one of the greatest challenges in the utilization of light for efficient and high-density microalgal cultivation . The details of this phenomenon should be intensively investigated by using computational fluid dynamics (CFD) technology in the future.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…As shown in Figure , remarkable turbulent flow mixing was found on the bottom culture surface where the spray culture spattered, and the area of turbulent flow was estimated to be approximately one-fifth of the total cultivation area. This result indicated that the proposed mixing mode could significantly increase the light-dark cycling frequency and mixing performance in a certain mixing time and k L a (O 2 ) (Figure ); light-dark cycling is one of the greatest challenges in the utilization of light for efficient and high-density microalgal cultivation . The details of this phenomenon should be intensively investigated by using computational fluid dynamics (CFD) technology in the future.…”
Section: Resultsmentioning
confidence: 95%
“…This result indicated that the proposed mixing mode could significantly increase the light-dark cycling frequency and mixing performance in a certain mixing time and k L a (O 2 ) (Figure 4); lightdark cycling is one of the greatest challenges in the utilization of light for efficient and high-density microalgal cultivation. 40 The details of this phenomenon should be intensively investigated by using computational fluid dynamics (CFD) technology in the future. Moreover, the diameters of the spray water could be controlled to rapidly and continuously vary at different sizes, thereby increasing the area of efficient turbulent mixing.…”
Section: Cultivation Performance Of the Scaled-up Tlf-pbrmentioning
confidence: 99%
“…In this respect, studies have been conducted to determine how to accurately quantify the impact of hydrodynamic characteristics on the infectivity of bacteriophage MS2, a norovirus surrogate. Several studies also involved the development of bioreactors for testing the effect of hydrodynamic characteristics on microalgae and human enteric viruses [29][30][31][32][33]. The results obtained from the studies indicated that the hydrodynamic cavitation could trigger the inactivation waterborne viruses to levels defined in water quality directives.…”
Section: Case Studies In Environmental and Biological Systemsmentioning
confidence: 99%
“…Biofouling/biofilms Turbulent Experimental/CFD [25][26][27][28][29][30] Water disinfection/irrigation Turbulent Experimental/CFD [31][32][33][34][35] Water self-purification Turbulent Experimental [43][44][45][46] Solid-liquid separation Turbulent Experimental [2,[36][37][38] Food and paper processing Turbulent Experimental [39][40][41][42] Table 2.…”
Section: Technical Application Flow Regime Study Type Referencesmentioning
confidence: 99%
“…To improve culture mixing conditions, such as light distribution and productivity, swirl mixing presents important characteristics to be taken into account 15,30,31 . The productivity in biomass increased between 30% and 80% compared with PBR without static mixers when using helical mixers, 30 cross mixers 10 or helical blade rotors 32 . Nevertheless, the use of static mixers also generates an increase in the pressure drop in the system and so in energy consumption.…”
Section: Introductionmentioning
confidence: 99%